2016
DOI: 10.30996/persona.v5i01.742
|View full text |Cite
|
Sign up to set email alerts
|

Dukungan Sosial, Efikasi Diri dan Resiliensi Pada Karyawan yang Terkena Pemutusan Hubungan Kerja

Abstract: This study aimed to determine the relationship between social support and selfefiaksi to employees affected by layoffs. The hypothesis of this study is that there is arelationship between social support and self-efficacy of employees affected by layoffs.This study was conducted on employees affected by layoffs at Semple number 70 usingrandom sampling techniques. Data collected through scale social support, self-efficacyscale and scale resilience of employees affected by layoffs. Data were analyzed withregressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The first hypothesis (H1) test showed that self-efficacy has a positive influence towards resilience; thus, the higher the self-efficacy play role to achieve the higher the resilience of local workers in non-star accommodation in Ubud, Bali after facing the Covid-19 pandemic. The results of this study are consistent with research that has been conducted by Aziz and Noviekayati (2016); Sulastri and Jufri (2021); Indrayanti et al (2022); Bozovic et al (2021), which stated that self-efficacy has a positive and significant influence on the resilience of workers in facing the Covid-19 pandemic, and in their research showed that self-efficacy plays an important role for an individual to determine how he behaves in responding to the difficult situations he faces. Resilient individuals also have self-efficacy that can be used as a resource to effectively manage problems or solve problems experienced by individuals.…”
Section: Discussionsupporting
confidence: 91%
“…The first hypothesis (H1) test showed that self-efficacy has a positive influence towards resilience; thus, the higher the self-efficacy play role to achieve the higher the resilience of local workers in non-star accommodation in Ubud, Bali after facing the Covid-19 pandemic. The results of this study are consistent with research that has been conducted by Aziz and Noviekayati (2016); Sulastri and Jufri (2021); Indrayanti et al (2022); Bozovic et al (2021), which stated that self-efficacy has a positive and significant influence on the resilience of workers in facing the Covid-19 pandemic, and in their research showed that self-efficacy plays an important role for an individual to determine how he behaves in responding to the difficult situations he faces. Resilient individuals also have self-efficacy that can be used as a resource to effectively manage problems or solve problems experienced by individuals.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are consistent with research that has been conducted by Sulastri & Jufri (2021), Indrayanti et al, 2022, andBozovic et al, 2022 which stated that self-efficacy has a positive and significant influence on the resilience of workers affected by the Covid-19 pandemic, and in their research stated that self-efficacy plays an important role for an individual to determine how he behaves in responding to the difficult situations he faces. Resilient individuals also have self-efficacy that can be used as a resource to be able to effectively manage problems or solve problems experienced by individuals (Aziz & Noviekayati, 2016). The Covid-19 pandemic has demanded non-star accommodation business community workers in the Ubud Village to turn to other sectors to find new solutions and alternatives to survival during a heavy economic downturn in the tourism sector.…”
Section: Discussionmentioning
confidence: 99%
“…Boatman (2014) juga beranggapan bahwa resiliensi akademik merupakan kekuatan dari dalam dan dari luar untuk mengatasi berbagai pengalaman kurang baik yang menekan dan berakibat menghambat proses dalam belajar, sehingga individu mampu beradaptasi dengan baik dan mampu menuntaskan tuntutan akademik secara optimal. Resiliensi merupakan kemampuan yang penting dalam mementukan keputusan yang sulit di waktu-waktu yang mendesak (Aziz & Noviekayati, 2016).…”
Section: Pendahuluanunclassified